INSL3/RXFP2 Signaling in Testicular Descent: Mice and Men - Feng, Shu (2009)
Mutations of the insulin-like 3 (INSL3) hormone or its receptor RXFP2 cause intraabdominal cryptorchidism in male mice. Specific RXFP2 expression in mouse gubernacula was detected at embryonic day 14.5 (E14.5) and markedly increased after birth in the developing cremaster muscle, as well as in the epididymis, testicular Leydig and germ cells. INSL3 treatment stimulated cell proliferation of embryonic gubernacular and Leydig cells implicating active INSL3-mediated signaling. The transcription factor SOX9, a known male sex determination factor, up-regulated the activity of the RXFP2 promoter. INSL3 is sufficient to direct the first transabdominal phase of testicular descent in the absence of hypothalamic-pituitary-gonadal axis signaling or Hoxa10 but their presence is important for inguinoscrotal testicular descent. Similarly, conditional ablation of the androgen receptor gene in gubernacular cells resulted in disruption of inguinoscrotal descent. We performed mutation screening of INSL3 and RXFP2 in human patients with cryptorchidism and control subjects from different populations in Europe and USA. Several missense mutations were described in both the INSL3 and RXFP2 genes. A novel V39G INSL3 mutation in a patient with cryptorchidism was identified, however the functional analysis of the mutant peptide did not reveal compromised function. In more than 2000 patients and controls analyzed to date the T222P RXFP2 mutation is the only one strongly associated with the mutant phenotype. The T222P mutant receptor transfected into 293T cells had severely decreased cell membrane expression, providing the basis for the functional deficiency of this mutation.